Genome-wide identification and expression analysis of MIKCC genes in rose provide insight into their effects on flower development - Wang, Yi; Yang, Tuo; Li, Yuqi; Hou, Jialin; He, Junna; Ma, Nan; Zhou, Xiaofeng (Frontiers in Plant Science, 2022)
The MIKCC-type gene family, plays an important role in plant growth, development, biotic and abiotic stress tolerance, especially during floral organ differentiation. However, there is currently lack of research on the chromosome level of MIKCC-type genes in rose, and its functional differentiation needs to be further explored. In this study, we conducted comparative research on MIKCC-type genes of MADS-box family. We demonstrated the phylogenetic tree and expression analysis of 42 MIKCC-type genes in rose, which were classified into 12 subfamilies. The expression of these genes was generally in accordance with the specific expression patterns of their predicted subfamily, indicating that the features of MIKCC-type genes were broadly conserved during the evolution of the rose. Collinear analysis of MIKCC genes among Rosaceae species confirmed the occurrence of whole genome duplications (WGD) and found some species-specific MIKCC genes. Transcriptome analysis also found that the expression of some MIKCC-type genes responded to low temperatures (4°C, 24 h) during flower organ differentiation. We inferred that these conserved, duplicated and novel expression patterns of MIKCC-type genes may play a vital role in the adaptation of rose to various internal and external environmental changes. This study provided a theoretical basis for future functional analysis of the MIKCC genes in rose and investigated the evolutionary pattern of the MIKCC gene family in the Rosaceae genome.